Peranan Pendidikan Agama Kristen dalam Keluarga guna Membendung Degradasi Moral Remaja Generasi Z di Era Disrupsi Teknologi - Sitanggang, Elisabet Vritze (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2024)
The era of technological disruption has had a significant impact on the lives of teenagers, especially those belonging to generation Z. This research aims to explain the importance of the role of Christian religious education in the family in order to stem the occurrence of moral degradation among generation Z teenagers. The era of technological disruption has resulted in generation Z teenagers , experienced various problems of moral decline. Without realizing it, generation Z teenagers who basically master technology, on the other hand, are also affected by the negative things it causes. Some teenagers bully via social media because information is easily spread without a clear filter as to whether the information is true or false. Other teenagers commit impolite and indecent actions, after watching meaningless content such as pranks and pornographic content on YouTube. This research uses a qualitative descriptive method, namely by collecting data related to titles through reference books and journals. Then describe it to find important points that result in moral degradation. The results of the analysis of the role of Christian Religious Education are formulated into concepts and explained. The results of the research show that Christian religious education in the family by teaching moral values based on the Bible, is able to stem the moral degradation of generation Z teenagers due to technological disruption.Era disrupsi teknologi memberi dampak yang signifikan kepada kehidupan para remaja khususnya mereka yang termasuk generasi Z. Penulisan ini bertujuan untuk menjelaskan pentingnya peranan Pendidikan Agama Kristen dalam keluarga guna membendung terjadinya degradasi moral diantara remaja generasi Z. Era disrupsi teknologi telah mengakibatkan kelompok remaja generasi Z, mengalami berbagai masalah penurunan moral. Tanpa disadari, remaja generasi Z yang pada dasarnya menguasai teknologi, disisi lain ikut terpengaruh dengan hal-hal negatif yang diakibatkannya. Beberapa remaja membullying melalui media sosial sehingga informasi yang belum jelas kebenarannya menjadi tersebar. Remaja lainnya melakukan aksi yang tidak sopan dan tidak senonoh, setelah menonton sebuah konten yang tidak berbobot seperti konten berbau asusila di Youtube. Penelitian ini menggunakan metode deskriptif kualitatif yakni dengan mengumpulkan data-data sehubungan dengan judul melalui buku-buku referensi, dan jurnal. Kemudian mendeskripsikannya untuk menemukan pokok penting yang mengakibatkan degradasi moral. Hasil analisis terhadap peran Pendidikan Agama Kristen dirumuskan menjadi konsep dan memaparkannya. Hasil penelitian menunjukkan bahwa